Structured Oral Examinations in Internal Medicine - Case H - Hani Almoallim; Ali Alkatheeri; Alaa Monjed; Fozya Basheer; Abdullah Tawakol; Ahmad Imam; Abdulsalam Noorwali; Kamran Hameed (Association of American Medical Colleges, 2009)
Abstract This resource is one component of the nine-part Structured Oral Examinations in Internal Medicine series. In this case (Case H: Systemic Lupus Erythematosus), a 21-year-old female college student presents to you with an 8 week history of joints pains. She is not married and her menstrual period is regular. She does not smoke. She takes ibuprofen for temporary relief. She has pericardial chest pain, hair loss, photosensitive rash, malar rash, and mouth ulcers. She has polyarthritis and lymphadenopathy by physical exam. She has hemolytic anemia, pericarditis, and glomerulonephritis. She has a positive antinuclear antibodies, anti-double-stranded DNA, and low complements. This approach of examination is very convenient to both students and examiners. It is structured and standardized. We were successfully able to avoid almost all disadvantages associated with a long case format. The majority of our students enjoyed the exam from personal and written feedback we received after the exam.